Development of Solid Waste Recovery Model for a University Using System Dynamics - Laytani, Ryan B.; Banquil, Benedict B. (JPAIR Multidisciplinary Research, 2012)
A solid waste recovery model for university is developed using system dynamics (SD). This model specifically focuses on cyclical cause-and-effect relationships about the solid waste system in University of Cebu. Dynamic behavior of three recovery policies, i.e. Policy 1: Recycling, Policy 2: Composting, and Policy 3: Recycling and Composting, is analyzed in the model using different field information and justified assumption. A software package called Vensim® is likewise utilized in designing the modeling structure, mapping the formulated equation, and performing the computer simulation. Vensim® is further used in generating graphics illustrating the system’s behavior during the first ten years of policy implementation, i.e. 2012-2022. Timeseries graphs suggest Policy 3 as most appropriate to be implemented in the university. Among the three policies, Policy 3 sets the least residual waste, greatest fund savings, and earliest break-even in the entire phase of simulation. Policy 3 is also the most environmentally effective, economically profitable, and socially acceptable among the three policies. Although Policy 3 entails an investment in setting a materials recovery facility (MRF), simulation results showed that it can be regained within 4.25 years of MRF productivity. This paper also recommends measures for model improvement and suggests initial.